Teaching and Learning Using Whatsapp: English Teachers' Perception - Yusuf Al Arief; Rizky Amelia; Eka Puteri Elyani (English Language Education Study Program of STKIP PGRI Banjarmasin, 2021)
Social media has become part of the lives of Indonesian teenagers today. Referring to a survey conducted by the Indonesian Internet Network Organizing Association (APJII) in 2017, young people dominate the internet users in Indonesia to adults with a percentage of 75.50 % in the age range of 13-18 years, and teachers must deal with this fact. The researchers were interested in using teenagers' addiction to these gadgets to support the learning process. In this study, researchers used descriptive qualitative methods and took English teachers in Banjarmasin as research. The research was conducted by holding social media training, focusing on WhatsApp to learn English. Next, the researchers asked the subjects to use WhatsApp in the teaching and learning process. Next, researchers distributed questionnaires to figure out the perception of teachers. As a result, it was found that: 1) WhatsApp was very useful as a learning medium, 2) Students were motivated to follow the learning process because they used something they like, 3) WhatsApp can also promote more interaction between students.